Intake of ultra-processed foods and asthenozoospermia odds: A hospital-based case-control study - Lv, Jia-Le; Wu, Qi-Jun; Wang, Xiao-Bin; Du, Qiang; Liu, Fang-Hua; Guo, Ren-Hao; Leng, Xu; Pan, Bo-Chen; Zhao, Yu-Hong (Frontiers in Nutrition, 2022)
Background The intake of ultra-processed foods (UPFs) has increased rapidly in recent years. Evidence has suggested that UPFs has adverse effects on several health outcomes. This study aimed to first evaluate the association between the intake of UPFs and asthenozoospermia odds. Methods A hospital-based case-control study including 549 cases and 581 controls was performed in the infertility clinics of Shengjing Hospital of China Medical University from June 2020 to December 2020. Dietary intake was assessed using a validated food frequency questionnaire. Food items were categorized by the NOVA classification system based on the degree of processing. Semen parameters were analyzed according to the World Health Organization guidelines. Results The highest tertile of UPFs intake (% of total energy intake) was positively associated with the odds of asthenozoospermia (odds ratio [OR] = 1.53; 95% confidence interval [CI]: 1.12, 2.10; P for trend < 0.05), compared with the lowest tertile. Similar patterns were also found in subgroup analyses among participants with age ≥32 years (OR = 1.58; 95% CI: 1.04, 2.40), BMI ≥ 24 kg/m2 (OR = 1.52; 95% CI: 1.04, 2.22), ever cigarette smoking (OR = 1.78; 95% CI: 1.14, 2.79), and ever alcohol drinking (OR = 1.65; 95% CI: 1.01, 2.72), and in sensitivity analyses by using absolute amount (g/day) to calculate the intake of UPFs. Conclusion Higher consumption of UPFs was positively associated with the odds of asthenozoospermia. More studies are needed to confirm our findings.